Corrosion protection challenges for Australia’s longest single-lane bridge in a harsh marine environment - Cheaitani Atef; Brown Bob; Lamperd Rhett (MATEC Web of Conferences, 2025)
The Mission River Bridge in Weipa, Queensland, is Australia’s longest single-lane bridge spanning 1040 meters. Built in 1971 with a 35-year design life, the bridge plays a key role in supporting the region’s mining operations and its local communities. Over time, its steel piles have suffered significant section loss due to Microbially Induced Corrosion (MIC) in the aggressive marine environment. To mitigate further degradation and extend the bridge’s service life, Impressed Current Cathodic Protection (ICCP) systems were installed. The composite piles, consisting of prestressed concrete in the upper section and steel in the lower section, are protected by the ICCP systems up to mid-tide level. A Mixed Metal Oxide (MMO) ribbon anode system was also installed to protect the atmospheric zones, including the piles and sections of the headstocks. This paper presents a case study on the cathodic protection systems implemented for this complex marine structure. It highlights the technical challenges posed by MIC and the harsh environmental conditions, and it critically examines the limitations of current cathodic protection standards in addressing protection criteria for similarly complex structures.